The thing around your neck - Adichie, Chimamanda Ngozi, 1977- (Nigeria : Farafina, 2009)
A collection of twelve stories includes the tale of a medical student in hiding with a poor Muslim woman, and a woman who discovers a devastating secret about her brother's death.
Cell one -- Imitation -- A private experience -- Ghosts -- On Monday of last week -- Jumping monkey hill -- The thing around your neck -- The American embassy -- The shivering -- The arrangers of marriage -- Tomorrow is too far -- The headstrong historian.
Keywords: Short stories, Nigerian (English); Nigeria -- Fiction; Bildungsromans